Plasmodium berghei bio-burden correlates with parasite lactate dehydrogenase: application to murine Plasmodium diagnostics. (December 2016) - De, Sai; Stanisic, Danielle; Rivera, Fabian; Batzloff, Michael; Engwerda, Christian; Good, Michael
Abstract Background The spectrum of techniques to detect malaria parasites in whole blood is limited to measuring parasites in circulation. One approach that is currently used to enumerate total parasite bio-burden involves the use of bio-luminescent parasites. As an alternative approach, this study describes the use of a commercial ELISA human parasite lactate dehydrogenase (pLDH) detection kit to estimate total parasite bio-burden in murine malaria models. Methods The cross reactivity of pLDH in a commercial human malaria pLDH diagnostic kit was established in different components of blood for different murine malaria models. The use of pLDH as a measure of parasite bio-burden was evaluated by examining pLDH in relation to peripheral blood parasitaemia as determined by microscopy and calculating total parasite bio-burden using a bio-luminescentPlasmodium berghei ANKA luciferase parasite. Results The pLDH antigen was detected in all four murinePlasmodium species and in all components ofPlasmodium -infected blood. A significant correlation (r = 0.6922, P value <0.0001) was observed between total parasite bio-burden, measured as log average radiance, and concentration of pLDH units. Conclusions This high throughput assay is a suitable measure of total parasite bio-burden in murine malaria infections. Unlike existing methods, it permits the estimation of both circulating and sequestered parasites, allowing a more accurate assessment of parasite bio-burden.